Efficacy of hyaluronic acid in the treatment of nasal inflammatory diseases: a systematic review and meta-analysis - Liu, Huixia; Chen, Yue; Wang, Huan; Luo, Xinyi; Xie, Dengpiao; Ji, Qing; Tian, Li (Frontiers in Pharmacology, 2024)
Background: Hyaluronic acid (HA), the main component of extracellular matrix, has ability to promote tissue repair and regulate inflammation. It is used in otolaryngology as an adjuvant treatment to alleviate postoperative nasal symptoms. However, there is currently insufficient evidence demonstrating the therapeutic efficacy of HA for patients with nasal inflammatory diseases (NID). Therefore, this study aimed to evaluate the efficacy and safety of topical HA in the treatment of NID patients without receiving operation.In this meta-analysis, comprehensive searches were conducted in PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science.Keywords searched included "hyaluronic acid", "sinusitis", "allergic rhinitis", "rhinitis" and "randomized controlled trials (RCTs)". The Cochrane Collaboration's "Risk of Bias Assessment" tool was used to assess the quality of the included trials, and meta-analysis was performed using Rev Man5.3 and Stata15 statistical software.Results: A total of 11 articles and 825 participants were enrolled. For the primary outcomes, the pooled results revealed that HA significantly improves nasal obstruction (SMD, -0.53; 95% CI, -0.92 to -0.14, P=0.008, I 2 = 79%) and rhinorrhea (SMD, -0.71; 95% CI, -1.27 to -0.15, P=0.01, I 2 = 90%) in patients with NID. As for the secondary outcomes, the pooled results demonstrated that compared with the control group, HA could significantly improve nasal endoscopic scores (p<0.05), rhinitis scores (p<0.05), rhinomanometry (p<0.05), nasal neutrophils (p<0.05), and mucociliary clearance (p<0.05). However, no significant differences were observed between the two groups regarding nasal itching, sneezing, hyposmia, quality of life scores, and nasal eosinophils. For risk of bias, 54.5% and 45.5% of trials had low risk of bias in randomization process, and in deviation of intended intervention, respectively.In present study, the result that HA might ameliorate symptoms of patients with NID. However, more clinical trials with large participants are needed to confirm this result.Systematic review registration number: CRD42023414539.